Recognition principle of the TAP transporter disclosed by combinatorial peptide libraries - Uebel, Stephan (The National Academy of Sciences of the USA, 1997)
Transport of peptides across the membrane of the endoplasmic reticulum for assembly with MHC class I molecules is an essential step in antigen presentation to cytotoxic T cells. This task is performed by the major histocompatibility complex-encoded transporter associated with antigen processing (TAP). Using a combinatorial approach we have analyzed the substrate specificity of human TAP at high resolution and in the absence of any given sequence context, revealing the contribution of each peptide residue in stabilizing binding to TAP. Human TAP was found to be highly selective with peptide affinities covering at least three orders of magnitude. Interestingly, the selectivity is not equally distributed over the substrate. Only the N-terminal three positions and the C-terminal residue are critical, whereas effects from other peptide positions are negligible. A major influence from the peptide backbone was uncovered by peptide scans and libraries containing d amino acids. Again, independent of peptide length, critical positions were clustered near the peptide termini. These approaches demonstrate that human TAP is selective, with residues determining the affinity located in distinct regions, and point to the role of the peptide backbone in binding to TAP. This binding mode of TAP has implications in an optimized repertoire selection and in a coevolution with the major histocompatibility complex/T cell receptor complex.